Otonomi Pendidikan Dan Kurikulum Berbasis Kompetensi Sebagai Jawaban Atas Realitas Kekinian - Naning Yuliani (ZAHRA: Research and Tought Elementary School of Islam Journal, 2020)
ABSTRACT The reform movement that wants a democratic social order in Indonesia has given birth to a national education system that is no longer centralistic. In a democratic education system, people are given the freedom to develop according to their abilities and potential. Recognition of the community to develop autonomously will spur the dynamics of society so that it becomes a developed society and science-powered. Thus, education autonomy will empower schools as the spearhead of the decentralization of education and encourage schools to improve quality in accordance with the potential of schools. Therefore, the government issued a school-based management policy and community-based education. along with the decentralized education system, it is necessary to apply a non-single curriculum that can be applied to all schools. A curriculum is needed that can be applied to schools according to the needs and abilities of the school. A single curriculum will encourage schools to increase creativity and high competitiveness so that superior and quality schools are born. In addition to the demands for decentralization, the national education system needs to be supported by a curriculum that can answer the current order, such as the demands of democratization, the challenges of the era of universalism, and the low quality of education in Indonesia. curriculum that can accommodate the demands of democratization will give birth to a new Indonesian society. namely civil society, fierce competition in the era of globalization requires a curriculum design that can lead the Indonesian people to achieve excellence in mastering science and technology. The low quality of education in Indonesia, one of which is due to curriculum patterns that are not able to equip students with life skills that shape creative, critical, independent and productive attitudes. Today's demands have given birth to a Competency Based Curriculum..